MODELING AND SIMULATION OF IMPROVED ENERGY MANAGEMENT SYSTEM - MS. SWATI UTTAM MORE; MRS. S. K. KAPDE (International Journal of Innovations in Engineering Research and Technology, 2021)
This paperdemonstrates the functionality of a power electronics based energy management system (EMS). The EMS includes batteries and a digitally controlled single phase voltage source inverter (VSI) which can be controlled as a current source or a voltage source depending on the status of the AC grid and the user’spreference. The EMS guarantees that the critical loads are powered when the AC grid fails; in which case the VSI is controlled as a voltage source. It also accomplishes peak power control by supplying battery power to the local loads while they are powered by the AC grid if the loads get large. The electricity cost savings accomplished by peak shaving are estimated